Property Lines in the Mind: Consumers’ Psychological Ownership and Their Territorial Responses - Kirk, Colleen P; Peck, Joann; Swain, Scott D (Journal of Consumer Research, 2018)
AbstractPsychological ownership, or the feeling that something is mine, has garnered growing attention in marketing. While previous work focuses on the positive aspects of psychological ownership, this research draws attention to the darker side of psychological ownership—territorial behavior. Results of five experimental studies demonstrate that when consumers feel psychological ownership of a target, they are prone to perceptions of infringement and subsequent territorial responses when they infer that another individual feels ownership of the same target. Potential infringers are held less accountable when they acknowledge ownership prior to engaging in otherwise threatening behaviors, and when they could not be expected to know that a target is owned, as it was not clearly marked. In addition, high narcissists are subject to a psychological ownership metaperception bias, and are thus more apt than low narcissists to perceive infringement. A multitude of territorial responses are documented for both tangible (coffee, sweater, chair, pizza) and intangible (a design) targets of ownership. Further, consumers infer the psychological ownership of others from signals of the antecedents of psychological ownership: control, investment of self, and intimate knowledge. Theoretical implications for territoriality and psychological ownership are discussed, along with managerial implications and areas for future research.